Aplikasi Perhitungan Pembagian Harta Warisan Dalam Islam Berbasis Web - Harmen Harmen; Omar Pahlevi; Tri Santoso (JURIKOM (Jurnal Riset Komputer), 2019)
The calculation of inheritance in Islam has begun to be forgotten, only a few people understand about this calculation, the complexity of this calculation makes people reluctant to carry out the division in accordance with Islamic law. In aspects of daily life problems often occur sometimes triggering disputes and causing family relationships to rift. Until now the community still needs a third party who can help calculate the distribution of inheritance, that is an expert, the calculation is done manually it is likely that there will be an error in the calculation results due to human negligence. The purpose of this research is to make an application that can help the community in dividing inheritance according to Islamic law. An application is a set of commands or code that is arranged systematically to execute a command given by humans. The system development method used is the Waterfall method. The author hopes that the presence of the Application of Calculation of Inheritance Distribution in Web-Based Islam is expected to help make it easier for the community to carry out the process of calculating inheritance in accordance with Islamic law so that inheritance law in Islam can be enforced as it should.